Experimental and numerical investigation of heat transfer from a narrow annulus to supercritical pressure water. (June 2015) - Wang, Han; Bi, Qincheng; Yang, Zhendong; Wang, Linchuan
Highlights: Heat transfer of supercritical water in a narrow annulus is investigated. Effects of system parameters and flow direction on heat transfer are studied. Deteriorated heat transfer is analyzed both experimentally and numerically. Abstract: Heat transfer characteristics of supercritical pressure water in a narrow annulus with vertically upward and downward flows were investigated experimentally and numerically. The outer diameter of the inner heated rod is 8 mm with an effective heated length of 620 mm. Experimental parameters covered the pressure of 23–28 MPa, mass flux of 400–1000 kg/m 2 s and heat flux on the outer surface of the heated rod from 200 to 1000 kW/m 2 . The general heat transfer behaviors were discussed with respect to various mass fluxes and pressures. According to the experimental data, it was found that the effect of flow direction on heat transfer depends on the heat-flux to mass-flux ratio ( q / G ). Heat transfer is much improved in the downward flow compared to that of upward flow at high q / G ratios. At the pressure of 25 MPa, low-mass-flux deteriorated heat transfer occurred in the upward flow but not in the downward flow. At the same test parameters, however, heat transfer deterioration was observed at both of the two flow directions when the pressure was lowered to 23 MPa. The experimental results indicate that buoyancy plays an important role for this type of deterioration, but is not the only mechanism that leads to the heat transfer deterioration. Three turbulence models were assessed against the annulus test data, it was found that the SST k-ω model gives a satisfying prediction of heat transfer deterioration especially for the case of downward flow. The mechanisms for the low-mass-flow heat transfer deterioration were investigated from the viewpoints of buoyancy and property variations of the supercritical water.